2015
DOI: 10.1016/j.brainresbull.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Enteric plexuses of two choline-acetyltransferase transgenic mouse lines: Chemical neuroanatomy of the fluorescent protein-expressing nerve cells

Abstract: We studied cholinergic circuit elements in the enteric nervous system (ENS) of two distinct transgenic mouse lines in which fluorescent protein expression was driven by the choline-acetyltransferase (ChAT) promoter. In the first mouse line, green fluorescent protein was fused to the tau gene. This contruct allowed the visualization of the fiber tracts and ganglia, however the nerve cells were poorly resolved. In the second mouse line (ChATcre-YFP), CRE/loxP recombination yielded cytosolic expression of yellow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…They may play various functions and are involved in all aspects of gastrointestinal physiology, such as motility, excretive activity, intestinal blood flow and ion transport [ 1 , 6 ]. Previous studies have shown that the same neuronal cells may contain even a few active substances, which usually play similar roles [ 7 , 8 ] and studies on the co-localization of these substances contribute to a better understanding of their functions.…”
Section: Introductionmentioning
confidence: 99%
“…They may play various functions and are involved in all aspects of gastrointestinal physiology, such as motility, excretive activity, intestinal blood flow and ion transport [ 1 , 6 ]. Previous studies have shown that the same neuronal cells may contain even a few active substances, which usually play similar roles [ 7 , 8 ] and studies on the co-localization of these substances contribute to a better understanding of their functions.…”
Section: Introductionmentioning
confidence: 99%